Discovery of a novel megakaryopoiesis enhancer, ingenol, promoting thrombopoiesis through PI3K-Akt signaling independent of thrombopoietin. (March 2022) - Wang, Long; Zhang, Ting; Liu, Sha; Mo, Qi; Jiang, Nan; Chen, Qi; Yang, Jing; Han, Yun-Wei; Chen, Jian-Ping; Huang, Fei-Hong; Li, Hua; Zhou, Jie; et al.
Abstract: Thrombocytopenia, a most common complication of radiotherapy and chemotherapy, is an important cause of morbidity and mortality in cancer patients. However, there are still no approved agents for the treatment of radiation- and chemotherapy-induced thrombocytopenia (RIT and CIT, respectively). In this study, a drug screening model for predicting compounds with activity in promoting megakaryocyte (MK) differentiation and platelet production was established based on machine learning (ML), and a natural product ingenol was predicted as a potential active compound. Then, in vitro experiments showed that ingenol significantly promoted MK differentiation in K562 and HEL cells. Furthermore, a RIT mice model and c-MPL knock-out (c-MPL -/- ) mice constructed by CRISPR/Cas9 technology were used to assess the therapeutic action of ingenol on thrombocytopenia. The results showed that ingenol accelerated megakaryopoiesis and thrombopoiesis both in RIT mice and c-MPL -/- mice. Next, RNA-sequencing (RNA-seq) was carried out to analyze the gene expression profile induced by ingenol during MK differentiation. Finally, through experimental verifications, we demonstrated that the activation of PI3K/Akt signaling pathway was involved in ingenol-induced MK differentiation. Blocking PI3K/Akt signaling pathway abolished the promotion of ingenol on MK differentiation. Nevertheless, inhibition of TPO/c-MPL signaling pathway could not suppress ingenol-induced MK differentiation. In conclusion, our study builds a drug screening model to discover active compounds against thrombocytopenia, reveals the critical roles of ingenol in promoting MK differentiation and platelet production, and provides a promising avenue for the treatment of RIT. Graphical Abstract: ga1 Highlights: A drug screening model is developed to predict active compounds in hematopoiesis. Ingenol promotes megakaryocyte differentiation in K562 and HEL cells. Ingenol exhibits a great therapeutical effects on thrombocytopenia. The action of ingenol is depend on PI3K-Akt, but independ on TPO/c-MPL signaling.